Open Banking Meets Islamic Finance: A Qualitative Content Analysis of Sharia – Compliant Digital Inclution - Hassany, Egha Ezar Junaeka Putra (Jurnal Magister Ekonomi Syariah, 2025)
While the global financial sector has rapidly embraced data openness to enhance financial inclusion, the Islamic finance industry continues to face a significant technological adoption gap. Open banking, as a new paradigm in the financial industry, presents a substantial opportunity to bridge this gap through data transparency and inter-institutional collaboration enabled by Application Programming Interfaces (APIs). However, its implementation within Islamic finance requires strict alignment with Sharia principles such as justice, transparency, and trust. This study aims to examine how open banking can be ethically and effectively integrated into the Islamic financial system. Employing a descriptive approach and an inductive-based Qualitative Content Analysis (QCA), data were collected through literature review, policy document analysis, and in-depth interviews with regulators, academics, and Islamic finance practitioners. The open and axial coding processes revealed four central themes: (1) the ethics of Sharia-Compliant data exchange, (2) strategic collaboration between Islamic banks and fintech firms, (3) regulatory and fiqh-related challenges in the digital context, and (4) the potential of Sharia-based financial inclusion. The findings indicate that open banking can catalyze digital transformation in Islamic finance, provided it is supported by adaptive fatwas, clear regulatory frameworks, and enhanced digital and Sharia literacy. The integration of open banking and Islamic finance is not merely a matter of technological adoption, but a transformative process that involves values and structures, demanding an interdisciplinary approach. Their synergy holds the potential to create a financial system that is inclusive, transparent, and aligned with the objectives of Maqashid al-Sharia.